2018
DOI: 10.1103/physreva.97.053605
|View full text |Cite
|
Sign up to set email alerts
|

Probing the exchange statistics of one-dimensional anyon models

Abstract: We propose feasible scenarios for revealing the modified exchange statistics in one-dimensional anyon models in optical lattices based on an extension of the multicolor lattice-depth modulation scheme introduced in [Phys. Rev. A 94, 023615 (2016)]. We show that the fast modulation of a two-component fermionic lattice gas in the presence a magnetic field gradient, in combination with additional resonant microwave fields, allows for the quantum simulation of hardcore anyon models with periodic boundary condition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 63 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…We conclude by discussing possible realizations of the model considered in this paper. Apart from theoretical ideas for realizing generalized statistics in one dimension [16][17][18][19][20] , systems of fermionic or bosonic atoms with density-dependent hoppings have been proposed theoretically [31][32][33][34][35][36][37][38][39] and realized experimentally 40,41 . The system studied in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude by discussing possible realizations of the model considered in this paper. Apart from theoretical ideas for realizing generalized statistics in one dimension [16][17][18][19][20] , systems of fermionic or bosonic atoms with density-dependent hoppings have been proposed theoretically [31][32][33][34][35][36][37][38][39] and realized experimentally 40,41 . The system studied in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Such generalizations can be introduced in many different ways, for instance, by modifying the conditions on the wave function and its derivative at the points when two of the particles have the same coordinate, modifying the commutation relations between the creation and annihilation operators in a second-quantized formalism, or modifying the form of the exclusion principle [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Several theoretical proposals have been made for realizing generalized statistics in one dimension [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…The tails of the momentum distribution exhibit the universal 1/k 4 behavior with the amplitude given by Tan's contact which is a monotonic function of the statistics parameter. The natural extension of our work is the consideration of the equivalent lattice system, the 2AHM [87,88], in the strong repulsive limit. In the fermionic case, the well known Hubbard model, the determinant representation of the correlators is already known [139,140] and the long distance asymptotics of the static correlators has also been determined [141].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we investigate the correlation functions of a 1D two-component system with repulsive contact interactions which can be understood as the anyonic generalization of the Gaudin-Yang model. The literature on 1D anyonic models has been growing steadily in the last years spurred by several experimental proposals of realizing such systems with ultracold atoms in optical lattices using Raman-assisted tunneling [84,85], periodically driven lattices [86] or multicolor lattice-depth modulation [87,88]. Much of the attention was focused on single component systems like the anyonic Lieb-Liniger model [89][90][91] for which we know the ground state characterization [90,92], asymptotic behavior of the correlation functions for homogeneous [26,27,59,[93][94][95] and trapped systems [96,97], entanglement [98,99], and nonequilibrium [100][101][102] properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we investigate the above issues in context of the paradigmatic Su-Schrieffer-Heeger (SSH) model for polyacetylene [10,11] that stabilises symmetry protected topological boundary modes. We examine an interesting tuning parameter that is of relevance in context of recent experimental [43,44] and theoretical [45][46][47] developments -the generalised algebra of the interacting fermions -and study it in context of two coupled SSH chains as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%